The Effect of Feeding Rubber Leaves Supplemented with Probiotics on Eggs Worm in Digestive Tract of Ettawa Cross Breed Goat: THE EFFECT OF FEEDING RUBBER LEAVES SUPPLEMENTED WITH PROBIOTICS ON EGGS WORM IN DIGESTIVE TRACT OF ETTAWA CROSS BREED GOAT (Universitas Djuanda Bogor, 2022)
This experiment was conducted to study the effect of feeding rubber leaves supplemented with probiotics (Bacillus pumilus st. L1) on the number of eggs worm and the prevalence of worms in the digestive tract of ettawa cross-breed goats. Twelve lactating ettawa cross-breed goats were allocated into three group using randomized block design to received fours experiment ration consist; P1 (0% rubber leaves + 60% native grass) + 40% concentrate, P2 ( 15% rubber leaves + 45% native grass) + 40% concentrate+ probiotics, P3: (30% rubber leaves + 30 % native grass) + 40% concentrate+ probiotics, and P4 (45% rubber leaves + 15% native grass) + 40% concentrate+ probiotics. The concentrate was formulated using 38% rice brans, 28% corn meal, 27% soybean meal, 5% coconut cake, 1% salt, and 1% minerals mix. Bacillus pumilus st. L1 with a concentration of 2.8 x 1017 CFU/ml was used as a probiotic source and supplemented with 1% in the ration. The variables measured were dry matter intake and the total of eggs worm per gram of feces. The data obtained were analyzed using analysis of variance (ANOVA) and continued with Duncan's Multiple Range Test. The experiment result showed that the increased use of rubber leaves supplemented with 1% probiotics had a significant (P<0.05) increase in dry matter intake (g/head/day), had a significant (P<0.05) decrease in the total of eggs worm, and increase percentage of the total of eggs worm reduced. The experiment result concluded that the use of 45% rubber leaves supplemented with 1% of probiotics ( Bacillus pumilus St. L1) in the rations had the ability to reduce egg worms up to 75% in the digestive tract of lactating ettawa cross-breed goats.